Ambient air pollution and risk of tuberculosis: a cohort study. Issue 1 (29th October 2015) - Lai, Ting-Chun; Chiang, Chen-Yuan; Wu, Chang-Fu; Yang, Shiang-Lin; Liu, Ding-Ping; Chan, Chang-Chuan; Lin, Hsien-Ho
Abstract : Objectives: Several respirable hazards, including smoking and indoor air pollution from biomass, were suggested to increase the risk of tuberculosis. Few studies have been conducted on ambient air pollution and tuberculosis. We investigated the association between exposure to ambient air pollution and incidence of active tuberculosis. Methods: We conducted a cohort study using 106 678 participants of a community-based screening service in Taiwan, 2005–2012. We estimated individual exposure to air pollution using data from the nearest air quality monitoring station and the road intensity within a 500 m buffer zone. The incidence of tuberculosis was ascertained from the national tuberculosis registry. Results: After a median follow-up of 6.7 years, 418 cases of tuberculosis occurred. Exposure to fine particulate matter (PM2.5 ) was associated with increased risk of active tuberculosis (adjusted HR: 1.39/10 μg/m 3 (95% CI 0.95 to 2.03)). In addition, traffic-related air pollution including nitrogen dioxide (adjusted HR: 1.33/10 ppb; 95% CI 1.04 to 1.70), nitrogen oxides (adjusted HR: 1.21/10 ppb; 95% CI 1.04 to 1.41) and carbon monoxide (adjusted HR: 1.89/ppm; 95% CI 0.78 to 4.58) was associated with tuberculosis risk. There was a non-significant trend between the length of major roads in the neighbourhood and culture-confirmed tuberculosis (adjusted HR: 1.04/km; 95% CI 0.995 to 1.09). Conclusions: Our study revealed a possible link between ambient air pollution and risk of active tuberculosis. Since people from developing countries continue to be exposed to high levels of ambient air pollution and to experience high rates of tuberculosis, the impact of worsening air pollution on global tuberculosis control warrants further investigation.